PROFESSIONAL SELF-CONCEPT AND ATTITUDES OF PARENTAL PARTICIPATION OF PEDIATRIC NURSES - SEVAL, Müge; KURT, Aylin (PEARSON JOURNAL, 2020)
It was aimed to evaluate the relationship between professional self-concept pediatric nurses units and attitudes of parental participation. This study was conducted with 87 nurses worked in pediatric units in two hospitals in Zonguldak-Turkey between January-April 2019. “Personel Information Form”, “Professional Self-Concept Scale in Clinician Nurses” and “Parent Participation Attitude Scale” were used. There was a positive correlation between the total score of the nurses from the Parental Participation Attitude Scale and the Professional Self-Concept Scale in Clinician Nurses and its subscales such as professional satisfaction (p=0.004), professional competence (p=0.002), professional attitude and skill (p=0.000) subscales and total score (p=0.000). Nurses’ attitudes respect parental participation are affected by professional self-concept. It was thought that family-centered care can be increased by increasing professional self-concept in nurses by providing the participation of nurses in more trainings and scientific studies.